Prediction of Complications and Death in Covid-19 Patients with Deranged Liver Function Tests at Time of Admission and Hospitalization - Muhammad Kamran, Mahtab Ahmad, Shehla Farhin, Sadia Yasir Khan, Saba Zafar, Tehmina Siddique, Samra Asghar, Sadia Khalil, Amber Shabbir, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
COVID-19 pandemic has affected millions of individuals globally over the last three years and is spreading continuously. In view of different studies and clinical findings, patients suffering with COVID-19 frequently have deranged liver function tests (LFTs), but the clinical significance of this finding is debatable. Objective: The present study was aimed to estimate the prevalence, features, and clinical significance of deranged LFTs in COVID-19 infected individuals, who were hospitalized but were not critically ill. Method: We conducted a cross sectional from May 2021 to December 2021 at The Akbar Niazi Teaching Hospital Islamabd. A total of 250 COVID-19 patients were included in the current study. The patient's blood samples were collected to get laboratory results, which included LFTs. LFTs were performed at the time of admission and every 5 ± 2 day throughout the stay. The outcome measure was either death or transfer of the patients to an intensive care unit. Results: At the time of admission, 160 patients (64%) showed deranged LFTs. Individuals with deranged LFTs experienced more severe inflammation, swelling, and organ damage than those who didn’t. Patients with deranged LFTs had a greater proportion of transfer to the ICU (81 vs 17), hospital stay (17 vs 7 days), and death (17 vs 5) than those with normal LFTs. Conclusion: The results of the current investigation demonstrated that LFTs data might forecast the degree of illness in patients with COVID-19 infections at the time of admission and during their hospital stay. Keywords: Covid-19, Liver Function Tests, ICU, Mortality Rate, Pakistan